Narcissistic Personality Disorder: Are Psychodynamic Theories and the Alternative DSM-5 Model for Personality Disorders Finally Going to Meet? - Schalkwijk, Frans; Luyten, Patrick; Ingenhoven, Theo; Dekker, Jack (Frontiers in Psychology, 2021)
“Narcissistic Personality Disorder is the new borderline personality disorder of our current era” (Choi-Kain, 2020). There have been recent developments on narcissism certainly worthwhile examining. Firstly, relational and intersubjective psychoanalysts have been rethinking the underlying concepts of narcissism, focusing on the development of self and relations to others. Secondly, in the DSM-5, the Alternative Model for Personality Disorders (AMPD) was presented for a dimensional evaluation of the severity of the personality disorder pathology. The combined dimensional and trait conceptualization of NPD opened the door to new integrated diagnostic perspectives, including both internal and interpersonal functioning. Finally, Pincus and Lukowitsky (2010) encourage clinicians to use a hierarchical model of pathological narcissism, as it opens up opportunities for shared points of interest in empirical research from different scholarly perspectives. As for most non-psychodynamic clinicians and researchers the DSM-5 clearly bears dominant weight in their work, we will take the AMPD model for NPD as our point of reference. We will discuss the narcissist’s unique pattern of self-impairments in identity and self-direction, and of interpersonal disfunctioning (evaluated by assessing empathy and intimacy). Subsequently, we will examine how contemporary psychodynamic theories and the hierarchical model of Pincus and Lukowitsky additionally inform or contradict the AMPD. For us, one of the big advantages of the AMPD is the use of structured clinical evaluations of disturbances of the self and interpersonal functioning and the dimensional evaluation of severity. As psychodynamic oriented therapists, we are enthusiastic about the opportunities for inclusion of psychodynamic concepts, but we also discuss a number of sticking points.